PELATIHAN PEMANFAATAN PLATFORM SOCIAL MEDIA MENUJU UMKM DIGITAL - Muhammad Saputra; Cahyani Pratisti; Rico Elhando Badri; Kurnia Fadila; Joko Triloka (Jurnal Abdi Insani, 2023)
Darmajaya Society Center (DSC) is one of the campus canteens located at the Darmajaya Institute of Informatics and Business (IIB Darmajaya). The results of observations made by the service team show an urgency for the implementation of science and technology where the business processes carried out by MSMEs related to recording, ordering and payment systems are still carried out manually. Another problem is that there has been a quite drastic decline in the sales turnover of canteen tenants or DSC MSMEs since the Covid 19 pandemic. The aim of this community service activity is to provide education to MSME players related to digitalization in terms of marketing and finance so that MSME players are able to use developing their business in a digital direction as a effort to increase sales. The activity implementation method used in MSME service activities at DSC is through the active participation method. The active participation method is a method of training and mentoring by identifying problems faced by partners. The results of the service activities carried out are in the form of increased understanding and knowledge of tenants or MSME actors as measured through pretests and posttests for each activity. The results of digital marketing and financial literacy training activities were obtained based on the posttest results of participants reaching an average score of 80% when compared with the average answer of participants in the pretest activity which only reached 40%. In the WhatsApp business training activity, participants obtained posttest results with understanding reaching an average of 70% compared to the average pretest answer which only reached 30%. In the training activity on using Qris, it was found that the posttest results reached an average of 80% when compared to the average answer of participants in the pretest activity which only reached 50%. The conclusion of this activity is the increasing understanding of tenants or MSME actors in the DSC IIB Darmajaya canteen regarding digital marketing and finance as well as the ability of DSC MSME actors to use WhatsApp business applications and non-cash financial applications or Qris.